The impact of innovation on the industrial enterprises’ cost in Ukraine - Synilova, A. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2021)
The article analyzes the impact of innovative development of industrial enterprises on the efficiency of their operation, namely on the cost of enterprises within the cost approach. The correlation-regression analysis of the dependence of enterprise value on the volume of innovation financing for industrial enterprises of Ukraine for the selected period of time, showed a direct relationship between the selected variables for analysis, and in combination with qualitative and quantitative analyzes confirmed the implementation of innovation. Scientific, journalistic, and static sources of information were used in the study. The subject of research in the article is the innovative development of enterprises in the context of the efficiency of enterprises, which is expressed in increasing the value of the company. The purpose of the article is to establish the dependence of the value indicator on such variables as the value of sold industrial products, the amount of funding for innovations for industrial enterprises, equity of industrial enterprises for the period 2008-2019. The paper aims to determine the role of innovation activities of enterprises within the innovation environment; to establish directions and forms of realization of innovative activity at the enterprises; analyze the dependence of cost indicators on the activity of innovation. The following methods are used: statistical, correlation-regression analysis, graphical. The following results were obtained: based on the analysis of the dynamics of changes in the main indicators of the value of industrial enterprises that implemented innovations, financed innovative development, the interdependence between increasing the value of companies and increasing the efficiency of innovation. The impact of the application of innovative development of enterprises in the context of maximizing its value is quantitatively calculated and proved. The article has proved the need for implementation and development of innovative activities in industrial enterprises in the formation of an innovative business strategy for the operation of economic entities, which is an important aspect of management decisions for company managers.